Identifying Potential to Promote the NOS in Elementary Science Teaching Packages - Karampelas, Konstantinos (International Journal of Learning, Teaching and Educational Research, 2018)
This paper aims to identify whether teaching the Nature of science is promoted in the teaching package of Greek Elementary School. Literature has justified that the nature of science is an important aspect of science teaching, which helps learners acquire a better understanding of science and its branches. Additionally, literature has suggested that for the nature of science to be taught, it is important for learners to get involved in activities, which emphasize on the epistemological aspect of science, the explanatory aspect of science, and the data issues aspect. However, research claims that the nature of science has not been effectively implemented in actual science teaching in many countries. A significant reason for that is the lack of the appropriate teaching material, such as teaching package. Through a qualitative approach with the help of the directed content analysis, this paper examines whether the science teaching package of Greek Elementary Curriculum emphasizes on the three basic aspects. The findings show that there is little emphasis. https://doi.org/10.26803/ijlter.17.6.1